(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
This article examines thematic groups in English psychology and related terms to them. There are nearly 30 psychological thematic groups in English psychology, however, this number increases day by day because new fields of psychology is emerging due to the needs in society.